(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
This is a first-person reflection of my journey through cultural humility to identify a connection between my inherent beliefs about Indigenous Peoples and Indigenous-specific systemic racism. The co-authors of this paper provided guidance, mentorship, and support in organizing the framework due to the challenging and sensitive nature of the content. As part of my relational practice, I worked with a Cree scholar to write this paper. As a descendant of white European colonial settlers, I grew up in a small community in Western Canada populated by people of similar backgrounds. My exposure to Indigenous Peoples and culture was very minimal; however, conversations and attitudes about Indigenous Peoples generally centered around negative and racist stereotypes. Childhood games and jokes insidiously contributed to the construction of my worldview by dehumanizing, belittling, and humiliating Indigenous Peoples. A necessary part of my journey was to recognize how these words and attitudes have informed my worldview and at the same time hurt Indigenous Peoples. Historical facts of Indigenous treatment were brushed off or minimized as something that happened in the past. Although sharing my experience is uncomfortable, I am compelled to identify and acknowledge how the deep-rooted beliefs and attitudes that I have towards Indigenous Peoples have been shaped by my education, culture, and experiences. I hope that my own developing journey with cultural humility may serve as a guide to deconstructing the historical, personal, and professional ways in which Indigenous-specific racism exists and is perpetuated in health care. My own first steps are an open invitation for the nursing profession to similarly begin to address unintentional and intentional racism in healthcare. By understanding Canadian history, committing to allyship, advocating for social justice, actively intervening by speaking up, and integrating trauma-informed care/principles into our practice, we may begin to effectively address Indigenous-specific racism in health care.